2006
DOI: 10.1093/toxsci/kfl139
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficient and Manganese Supplemented Diets Alter Metals and Transporters in the Developing Rat Brain

Abstract: Manganese (Mn) neurotoxicity in adults can result in psychological and neurological disturbances similar to Parkinson's disease, including extrapyramidal motor system defects and altered behaviors. Iron (Fe) deficiency is one of the most prevalent nutritional disorders in the world, affecting approximately 2 billion people, especially pregnant and lactating women, infants, toddlers, and adolescents. Fe deficiency can enhance brain Mn accumulation even in the absence of excess Mn in the environment or the diet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 45 publications
3
70
0
1
Order By: Relevance
“…Mn exposure has been shown to affect tissue concentrations in a differential manner depending upon species and type of exposure. A significant increase in striatal GABA due to Mn exposure was found in rats (Garcia et al 2006(Garcia et al , 2007Gwiazda et al 2002); while a marginally significant (P < 0.1) decrease in pallidal GABA concentrations in monkeys exposed to airborne MnSO4 has been reported (Struve et al 2007); and no statistical difference was found in brain regional GABA concentrations in primates injected with Mn intravenously (Burton et al 2009). While tissue GABA concentrations can capture the overall status of GABA biology in an organism, it does not fully reflect the extracellular concentrations which are critical for neurotransmission.…”
Section: Effects Of Mn On γ-Aminobutyric Acidmentioning
confidence: 90%
See 1 more Smart Citation
“…Mn exposure has been shown to affect tissue concentrations in a differential manner depending upon species and type of exposure. A significant increase in striatal GABA due to Mn exposure was found in rats (Garcia et al 2006(Garcia et al , 2007Gwiazda et al 2002); while a marginally significant (P < 0.1) decrease in pallidal GABA concentrations in monkeys exposed to airborne MnSO4 has been reported (Struve et al 2007); and no statistical difference was found in brain regional GABA concentrations in primates injected with Mn intravenously (Burton et al 2009). While tissue GABA concentrations can capture the overall status of GABA biology in an organism, it does not fully reflect the extracellular concentrations which are critical for neurotransmission.…”
Section: Effects Of Mn On γ-Aminobutyric Acidmentioning
confidence: 90%
“…It should be stressed that Fe deficiency affects about 2 billion subjects (Garcia et al 2007) and is a risk factor for Mn neurotoxicity even in absence of relevant exogenous exposures. Mn toxicity from various sources has been repeatedly reported in children (Fell et al 1996;Herrero Hernández et al 2003;Komaki et al 1999;Woolf et al 2002), including cognitive effects (Wasserman et al 2006).…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Reports at some labs shows death rate as high as 50% at doses required to lower blood sugars [17]. Vanadium has been shown to cause death in both pregnant rats (45%) and fetuses [18]. In addition, different labs have produced different outcomes related to the blood sugars, with some labs finding little blood sugar lowering effect.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have shown that dysregulation of iron homeostasis can affect Mn metabolism and induce toxicity [102][103][104]. Iron-deficient animals have enhanced Mn absorption due to increased iron transporters expression [105,106].…”
Section: Hereditary Hemochromatosismentioning
confidence: 99%
“…Accumulating evidence has indicated that the absorption of Mn is altered by body iron status [103,168]. For example, iron deficient anemia increases intestinal absorption of Mn, whereas iron overload conditions decrease Mn uptake [107,169].…”
Section: Gastrointestinal Uptakementioning
confidence: 99%